2017
DOI: 10.1016/j.jtho.2017.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Cranial Irradiation (PCI) versus Active MRI Surveillance for Small Cell Lung Cancer: The Case for Equipoise

Abstract: Prophylactic cranial irradiation (PCI) for SCLC offers a consistent reduction in the incidence of brain metastases at the cost of measurable toxicity to neurocognitive function and quality of life, in the setting of characteristic pathologic changes to the brain. The sequelae of PCI have historically been justified by the perception of an overall survival advantage specific to SCLC. This rationale has now been challenged by a randomized trial in extensive-stage SCLC demonstrating equivalent progression-free su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 82 publications
0
44
0
Order By: Relevance
“…9 After the official publication of the JCOG trial, 16 the controversy over administration of PCI in patients with ES-SCLC was increased. [27][28][29] In the present study, a sensitivity analysis excluding a JCOG study showed that patients who were treated with PCI showed an OS advantage compared to those treated without PCI. Our interpretation of the results of sensitivity analysis is as follows.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…9 After the official publication of the JCOG trial, 16 the controversy over administration of PCI in patients with ES-SCLC was increased. [27][28][29] In the present study, a sensitivity analysis excluding a JCOG study showed that patients who were treated with PCI showed an OS advantage compared to those treated without PCI. Our interpretation of the results of sensitivity analysis is as follows.…”
Section: Discussionmentioning
confidence: 53%
“…Unless brain imaging was a standard component of initial staging with the incorporation of brain MRI, a substantial number of patients might already have brain metastases at randomization. 27 Therefore, improved OS in some patients may be affected by the efficacy of whole-brain irradiation for known brain metastasis. 27 In line with this hypothesis, our pooled estimates for trials that did not confirm the absence of brain metastases at baseline revealed improvement in OS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in both groups). 11,12 Consequently, there is a clear need for new PCI trials performed in the MRI era. In LS-SCLC, a recent U.S. survey of practice showed that most (n ¼ 309) radiation oncologists recommend PCI (98%) and brain MRI before treatment (96%).…”
Section: Discussionmentioning
confidence: 99%
“…A recent Japanese study suggested that a policy of observation and regular surveillance with brain MRI may be an equally effective strategy to PCI in patients with extensive disease in terms of survival, without exposing every patient to the risks of radiation-induced neurocognitive dysfunction (2). This has led to proposals for a trial of PCI versus active surveillance with MRI in patients with limited stage SCLC (3). But what form should the PCI take?…”
Section: Interview (Figure 3)mentioning
confidence: 99%